BINARY OPPOSITIONS: A TOOL TO PROMOTE UNDERSTANDING AND TOLERANCETOWARDS THE MARGINALIZED - Lany Kristono (Indonesian JELT, 2010)
Triggered by the recent armed conflicts in different Indonesian societies and inspired by teacher’s strategic position to utilize education for peace, this study was conducted to help students indirectly contribute for a less conflicting environment. Since conflict is a result of disagreements in needs or necessities, which implies privileged and less-privileged groups, structuralism, particularly binary oppositions, was utilized. Implied in most first things one learns, binary oppositions are often taken for granted as how things are and should be; and thus, are ideological. In a norm-oriented society such as Indonesia, such a mindset may lead to unfairly labeling or judging the different others. Therefore, the 32 Prose students participating in this study were asked to utilize what they had learned in class to scrutinize the prevailing binary oppositions and labels and to present their findings in a collage group seminar, in which they   also received comments and answered questions from the audience. The presentation was followed by the participants’ individual written report of their analysis of the labels and their underlying ideologies. The essays revealed  most students’ critical questioning of the unfair judgments found in their society and the reasons behind them; thus, a stepping stone to better understand and tolerate the marginalized. Keywords:      Binary oppositions, marginalized, privileged, underlying ideology